A Homogenous, Photocrosslinkable Poly(dimethylsiloxane‐co‐methylvinylsiloxane) Solution in an Acrylate Monomer. Issue 1 (16th January 2023) - Park, Seung Koo; Park, Bong Je; Shin, Eun Jin; Choi, Meejeong; Park, Suntak; Shin, Hyung Cheol
Abstract : Front Cover : In article 2200509, Seung Koo Park, Hyung Cheol Shin, and co‐workers establish a photocrosslinkable, solvent‐free, homogenous poly(dimethylsiloxane) (PDMS) solution in tert‐butyl acrylate by calculating 3D distances of solubility parameter ( Δ δ ¯ $\overline {Δ δ}$ ) between PDMS and several liquid monomers. PDMS solid materials can be repeatably, continuously obtainable upon UV‐irradiation of the solution. The replicas made of PDMS could be mass‐produced even with a 3D inkjet printer in various applications.